Genome Destabilization Upon Exposure to Ionizing Radiation and During Acute Blood Loss - V. L. Kozhura; N. V. Kondakova; S. I. Zaichkina; O. M. Rozanova (Общая реаниматология)
The paper compares the currently available cytogenetic methods (chromosomal aberration test and micronuclear (MN) test) for the evaluation of the impact of stressors, by using ionizing radiation as an example. The experimental findings have led to the conclusion that the MN test shows the status of genome and reveals lesions upon very weak exposures. The MN test has demonstrated that hemic hypoxia and reinfusion, as other stressors, cause genetic material destabiliza-tion.